Ensino de língua portuguesa : uma reflexão voltada às competências discursivas - Marcolin, Letícia Regina (2022)
The teaching of Portuguese Language is frequently confused with the teaching of grammatical nomenclatures. However, there is a difference between them, considering that language is more than just conceptualization and norms, it is a mechanism of social interaction. In view of this, the question that guides the study is: what is, in fact, teaching the Portuguese Language at school? In consideration of it, the present work seeks to clarify the difference between Portuguese Language teaching and grammatical nomenclature teaching, reflecting on how grammar is involved in language use and can be explored in school activities with a view to the effective development of students' discursive skills. The present study is configured as a bibliographical and documentary research, since the discussions are based on studies by Possenti (1996), Neves (2019), Oliveira (2010), Geraldi (2006) and Fiorin (2007), in addition to the normative document of education in the national territory, the National Common Curricular Base - BNCC (BRASIL, 2018). The study points out that more important than teaching grammatical nomenclatures to students, language classes need to promote the development of discursive skills associated with social practices, so that subjects know how to read, analyze, and produce texts/utterances through which they interact with each other.